Sistem Informasi Pendataan Alat Bantu Bagi Penyandang Disabilitas Pada Dinas Sosial Kabupaten Labuhanbatu - Hasibuan, Ardiansyah; Nasution, Marnis; Ritonga, Irmayanti (Jurnal Informatika, 2024)
Introduction the development of technology in recent years is very rapid. The development of technology today is used by many parties in carrying out daily life. The data collection that received a lot of attention was related to the data collection of supplies for people with disabilities at the Labuhanbatu District Social Office. Currently, people with disabilities are getting special attention from various parties, both government and non-governmental organizations. The fulfillment of the rights of persons with disabilities continues to be championed by a number of parties which will then be submitted to the government, in this case the Labuhanbatu District Social Office. Therefore, the Social Service of Labuhanbatu Regency really needs a computerized information system to facilitate the work. Processing large amounts of data is certainly very difficult without a support system in it. This encourages many parties to take advantage of the development of information systems to the fullest, both information that comes from within and information that comes from outside. Based on the observations of the researchers found that employees of the Labuhanbatu District Social Service to collect data on disability aids is still manually by recording and then input into microsoft office either microsoft word or microsoft excel. This makes long work and data accuracy ineffective. Therefore, the researchers felt that a computerized information system is needed that can facilitate and accelerate the work and can make the work of collecting disability aids by employees at the Labuhanbatu District Social Service more effective. Waterfall to implement interface design, user interface design design using a programming language .